1995
DOI: 10.1148/radiology.195.3.7754021
|View full text |Cite
|
Sign up to set email alerts
|

Chronically stressed wrists in adolescent gymnasts: MR imaging appearance.

Abstract: Physeal cartilage extension into the metaphysis represents a healing sign in chronically stressed adolescent wrists. MR imaging findings including horizontal fracture and physeal cartilage extension to the metaphysis suggest that physeal widening occurred secondary to metaphyseal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(36 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…MRI revealed bone marrow edemalike signal in the medial clavicle extending from the physis into the metadiaphysis, reflecting an osseous stress reaction. These changes are similar to the ricketslike changes described as a ''gymnast wrist'' [12,19]. This study was interpreted by our musculoskeletal radiologist as being consistent with a stress lesion of the proximal left and right clavicular physes.…”
Section: Case Reportsupporting
confidence: 79%
“…MRI revealed bone marrow edemalike signal in the medial clavicle extending from the physis into the metadiaphysis, reflecting an osseous stress reaction. These changes are similar to the ricketslike changes described as a ''gymnast wrist'' [12,19]. This study was interpreted by our musculoskeletal radiologist as being consistent with a stress lesion of the proximal left and right clavicular physes.…”
Section: Case Reportsupporting
confidence: 79%
“…The words bone bruise, bone contusion, occult fracture and occult osseous lesion have been used synonymously for areas in cancellous bone, showing low signal intensity on T1-weighted and high signal intensity on T2-weighted MRI (Mink and Deutsch 1989, Deutsch et al 1990, Kier et al 1991, Stallenberg et al 1993, Escalas and Curell 1994, Laorr et al 1995, Shih et al 1995, Stein et al 1995, Zeiss et al 1995. It has been suggested that they represent a spectrum of radiographically occult bone injuries, ranging from bleeding, infarction and edema to microscopic compression fractures of cancellous bone (Kier et al 1991, Zeiss et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…The articular cartilage was normal. Since then, bone bruise injuries have been reported frequently in the knee (Mink and Deutsch 1989, Vellet et al 1991, Murphy et al 1992, Stallenberg et al 1993, Stein et al 1995, Zeiss et al 1995, Rangger et al 1996 and also in the wrist, the calcaneus, the foot and ankle, and in the hip (Kier et al 1991, Laorr et al 1995, Shih et al 1995, Soudry and Mannting 1995.…”
Section: Bone Bruise Of the Knee Histology And Cryosections In 5 Casesmentioning
confidence: 99%
“…Radiographs can show the ulnar plus deformation as well as widening and irregularity of the physis, narrowing of the epiphysis and sclerosis or cystic changes in the metaphysis [19]. If inconclusive, MRI can depict physeal cartilage extension into the metaphysis, bone bruise or vertical fractures [20].…”
Section: Wrist/handmentioning
confidence: 99%